Maternal Age and Preterm Births in Singleton and Twin Pregnancies Conceived By In Vitro Fertilisation in the United States. Issue 1 (5th December 2014) - Xiong, Xu; Dickey, Richard P.; Pridjian, Gabriella; Buekens, Pierre
Abstract Background Among natural conceptions, advanced maternal age (≥35 years) is associated with an increased risk of preterm birth. However, few studies have specifically examined this association in births resulting from in vitro fertilisation (IVF). Methods A retrospective cohort study was conducted in 97 288 singleton and 40 961 twin pregnancies resulting from fresh non‐donor IVF cycles using 2006–10 data from the Society for Assisted Reproductive Technology Clinic Online Reporting System. Results Rates of very early preterm (<28), early preterm (<32), and preterm birth (<37 completed weeks) decreased with increasing maternal age in both singleton and twin births (PTrend <0.01). With women aged 30–34 years as the reference, those aged <30 years were at an increased risk of all types of preterm births. The adjusted odd ratio (95% confidence interval [CI]) for very early preterm birth, early preterm birth, and preterm birth in women aged 25–29 years were 1.3 [95% CI 1.1, 1.5], 1.2 [95% CI 1.1, 1.4], and 1.1 [95% CI 1.02, 1.2] in singletons. This increased risk of preterm births among younger women was even more significant in twin births. However, women aged ≥35 years were not at an increased risk of any type of preterm births in both singleton and twin births. Conclusions In contrast to natural conception, advanced maternal age is not associated with an increased risk of preterm births in pregnancies conceived by IVF. Women who seek IVF treatments before 30 years old are at higher risk of all stages of preterm births.